An Investigation into Linguistic Devices of Declarations in Diplomatic Texts in English and Vietnamese - Huỳnh Anh Hồng (2011)
This research paper deals with the linguistic features of the declarations in the texts of diplomacy in English versus Vietnamese in terms of syntax, semantics and pragmatics. On the base ….